Examination of Genre-based Strategy Instruction in Middle School English Language Arts and Science - Traga Philippakos, Zoi A.; MacArthur, Charles A. (The Clearing house, 2021)
The purpose of the study was to examine the effects of an instructional intervention and its professional development (PD) on the opinion and argumentative writing of middle school students and on teachers' instructional delivery. The study utilized a design-based methodology and collected qualitative and quantitative data in order to identify revisions needed. Participants were 17 English Language Arts (ELA) and eight science teachers in a rural setting. Students' writing was assessed in ELA and science (n = 563 and n = 159, respectively) and teachers were interviewed at posttest. Results showed that writing quality improved overall from pretest to posttest (p < 0.001) and teachers found feasible and effective the instructional approach and commented positively on the PD components. Inhibiting factors and revisions from Cycle 1 to Cycle 2 are described while implications for research and practice on PD and curriculum design are further discussed.